Pulmonary embolism - assessment of risk factors and emboli locations - Mateusz Komisarczuk; Michał Kaczor; Ewa Kopyto; Mateusz Woch; Piotr Piech (Kazimierz Wielki University, 2020)
INTRODUCTION: Pulmonary embolism (PE) is a widespread disorder, which appears as a result of closure or restriction of main pulmonary artery or its branches and is often associated with deep vein thrombosis (DVT).The severity and clinical picture is frequently erratic and what is worrying it is a major cause of hospitalization and mortality in Europe.   OBJECTIVE: The mainpurpose of our study was to demonstrate meaning of emboli location in prognosis,favour risk factors which could be overlooked by clinicians and help to avoid further misdiagnosis.   ABBREVIATED DESRCIPTION OF THE STATE OF KNOWLEDGE:We highlighted the importance of defining a genetic profile, personal and family history of VTE, especially in patients with atypical pulmonary symptoms. Moreover, the awareness of possible occurring PE among children,during serious infections or in patients with malignancy is still insufficient. Furthermore, according our analysis clinical symptoms in patients with pulmonary embolism are undoubtedly influenced by the location.The more massive the thrombus appears, the more serious consequences can be expected for the patient.Along with the size of the thrombus, the risk of its complications increases because of haemodynamic changes.   SUMMARY:Diagnosing of pulmonary embolism in hemodynamically stable patients is still challenging for clinicians. There were many attempts to find significant and unmistakeable relationship between emboli location in pulmonary vasculature and prognosis.That knowledge could be helpful for clinicians in setting accurate diagnosis, implementing appropriate treatment and avoid possible life-threatening consequences.Risk stratification is crucial to the management and prognosis of patients with acute PE.